EXTRACURRICULAR WORK WITH YOUTH AS A MEANS ADAPTATIONS TO TEACHING TEACHING DISCIPLINE IN PROFESSIONAL CONDITIONS TEACHING - M.H. Viyevska (Academy of Cognitive and Natural Sciences, 2000)
The article reveals the problems of students' after-school activities and adjusting of first-grade students to the process of education in higher school. The leading role of the core chairs and the forms of after-school activities on psychology and pedagogy in the higher educational establishment of the economy have been confirmed. The schedule of tutorial work for the first-grade students are proposed.